New Approach for Mapping Land Cover from Archive Grayscale Satellite Imagery - Mohamed Rabii Simou; Mohamed Maanan; Safia Loulad; Mehdi Maanan; Hassan Rhinane (Technologies)
This paper examines the use of image-to-image translation models to colorize grayscale satellite images for improved built-up segmentation of Agadir, Morocco, in 1967 and Les Sables-d’Olonne, France, in 1975. The proposed method applies advanced colorization techniques to historical remote sensing data, enhancing the segmentation process compared to using the original grayscale images. In this study, spatial data such as Landsat 5TM satellite images and declassified satellite images were collected and prepared for analysis. The models were trained and validated using Landsat 5TM RGB images and their corresponding grayscale versions. Once trained, these models were applied to colorize the declassified grayscale satellite images. To train the segmentation models, colorized Landsat images were paired with built-up-area masks, allowing the models to learn the relationship between colorized features and built-up regions. The best-performing segmentation model was then used to segment the colorized declassified images into built-up areas. The results demonstrate that the Attention Pix2Pix model successfully learned to colorize grayscale satellite images accurately, improving the PSNR by up to 27.72 and SSIM by 0.96. Furthermore, the results of segmentation were highly satisfactory, with UNet++ identified as the best-performing model with an mIoU of 96.95% in Greater Agadir and 95.42% in Vendée. These findings indicate that the application of the developed method can achieve accurate and reliable results that can be utilized for future LULC change studies. The innovative approach of the study has significant implications for land planning and management, providing accurate LULC information to inform decisions related to zoning, environmental protection, and disaster management.